(untitled) (Global Journal of Medical Research, 2021)
The research work conducted to evaluate microbial load in poultry meat from different retail markets in the Khulna district (Nirala, Dumuria, and Fultola). The objective of the present study was to get quality poultry products from commercial farms and retail markets. A total of 48 samples collected and brought to Quality Feed Lab. for laboratory assay. Samples were propagating in nutrient agar followed by culture on selective media, Eosin Methylene Blue Agar, Mac-Conkey agar, Brilliant Green Agar, Salmonella-Shigella Agar. Total numbers of 48 samples examined, and 30 samples were found positive to E. coli, and the prevalence of E. coli in this study was 62.20 %. 37.50% of thigh meat samples were positive for E. coli within 24 tested samples whereas 87.50% of breast meat samples were positive within 24 tested samples for this bacteria. On the other hand, 23 samples were found positive for Salmonella spp, and the prevalence of Salmonella spp in this study was 49.91 %. 29.16% of thigh samples were positive for Salmonella spp within 24 tested samples whereas 66.66% of litter samples were positive within 24 tested samples for this bacteria. Total Viable Count (TVC), Total Coliform Count (TCC), Total Salmonella Count (TSC), and Total Campylobacter Count (CPC) in meat samples of different broiler markets like Nirala market at Khulna city corporation, Dumuria, and Fultola were determined.